Transfer of the Panamanian species Calathea gordonii to the genus Goeppertia (Marantaceae) - Silva, Felipe De Araújo; Braga, João Marcelo Alvarenga (Phytotaxa, 2016)
Calathea gordonii is herein transferred to Goeppertia. This genus was recently resurrected to incorporate most Calathea species. In preparation for the Flora Mesoamericana, C. gordonii was recently described as endemic to Panama and included in the Calathea sect. Breviscapus a section where all species have been transferred to Goeppertia.